Assessing the Private Sector and Civil Society Engagement in Poliomyelitis Myelitis Vaccination among Internally Displaced People in Khartoum State, 2019 - Amira A. M. Salih; Layla S. E. Abdeen; Amna S. M. Salih (Public Health, 2025)
BackgroundPoliomyelitis is an oro-fecal vaccine preventable disease affecting mainly children under five-years-old and is prevalent in poor sanitation and hygiene environment. The World Health Organization (WHO) stressed the need for coordination between the public and the non-governmental (particularly private) sectors to increase the coverage with immunization. This study aims to assess the private sector and civil society engagement in the implementation of poliomyelitis vaccination among internally displaced people and irregular settlement in Khartoum. Specifically, the study aimed to identify the major gaps in immunization program among internally displaced people (IDP), and to determine the enablers and barriers for the private sector and civil society active engagement in the immunization program.MethodsThis cross-sectional study used both quantitative and qualitative methods. Data was collected from the health facilities mangers and the expanded program of immunization (EPI) service providers at private and civil society’s facilities in the targeted areas using a semi-structured interview guideline and a self-administered questionnaire respectively. The obtained quantitative data was coded and then analyzed using the statistical package for social science (SPSS version 21) and presented using tables. For qualitative part, all data were transcribed verbatim and analyzed using a thematic analysis, paying particular attention to axes of difference, including gender, private center and non-governmental organization.ResultsThe major gaps were the insufficient number of health facilities together with uneven distribution of the available ones, and unclear mandate of non-governmental organizations (NGOs) and private sector in EPI programme. Most of the managers complained from the lack of human resources for vaccination but stressed on the fact that training of the existing staff made the availability of the service easier. Twelve (12) out of 23 health facilities visited by the field team where in areas that do not have electricity or water supply which imposed more efforts to preserve the vaccines. ConclusionPrivate and civil societies were not well utilized by EPI program in Khartoum, Sudan. A clear mandate for engagement and periodic training for the service providers is highly needed.